Eugenol@natural Zeolite vs. Citral@natural Zeolite Nanohybrids for Gelatin-Based Edible-Active Packaging Films - Achilleas Kechagias; Areti A. Leontiou; Yelyzaveta K. Oliinychenko; Alexandros Ch. Stratakos; Konstantinos Zaharioudakis; Katerina Katerinopoulou; Maria Baikousi; Nikolaos D. Andritsos; Charalampos Proestos; Nikolaos Chalmpes; Aris E. Giannakas; Constantinos E. Salmas (Gels)
In this study, aligned with the principles of the circular economy and sustainability, novel eugenol@natural zeolite (EG@NZ) and citral@natural zeolite (CT@NZ) nanohybrids were developed. These nanohybrids were successfully incorporated into a pork gelatin (Gel)/glycerol (Gl) composite matrix using an extrusion–compression molding method to produce innovative active packaging films: Gel/Gl/xEG@NZ (where x = 5, 10, and 15%wt.) and Gel/Gl/xCT@NZ (where x = 5 and 10%wt.). All films exhibited zero oxygen barrier properties. Release kinetic studies showed that both EG@NZ and CT@NZ nanohybrids adsorbed up to 58%wt. of their respective active compounds. However, EG@NZ exhibited a slow and nearly complete release of eugenol, whereas CT@NZ released approximately half of its citral content at a faster rate. Consequently, the obtained Gel/Gl/xEG@NZ films demonstrated significantly higher antioxidant activity as measured by the 2,2-diphenyl-1-picrylhydrazylradical (DPPH) assay and superior antibacterial effectiveness against Escherichia coli and Listeria monocytogenes compared to their CT-based counterparts. Overall, the Gel/Gl/xEG@NZ films show strong potential for applications as active pads for fresh pork ham slices, offering zero oxygen permeability, enhanced antioxidant and antibacterial properties, and effective control of total viable count (TVC) growth, maintaining a low and steady rate beyond the 10th day of a 26-day storage period.